The Compressive Strength Of Concrete Using Kakawate (Gliricidia Sepium) Jacq. Kunth Ex Walph. Wood Ash Cement - Rabena, Alfredo R.; Aman, Nelia V.; Amistad, Franklyn T. (JPAIR Multidisciplinary Research, 2010)
The acceptable disposal waste such as ash and sludge is a growing problem. A related problem is the recycling of other waste materials such as tires, glass and plastics. Because of the high-volume of kakawate tree in the region and that ash of kakawate wood is considered waste taken from dirty kitchen of every household, the researchers as engineers are pressured to recycle the ash for admixture construction material for low-cost housing projects. The researchers developed a methodology for determining the compressive strength of concrete cylinder mixed with kakawate (Gliricidia sepium) Jacq. Kunth ex walph using the proportion 20% ash and 80% cement for the mixture 1:2:3. The result of the laboratory testing can be a basis in proceeding with other proportions. Information is needed about the wood material’s physical properties. Further, environmental and waste management issues must be discussed as basis for the acceptability and practicability of waste and recycled material (WRMs). Developed mixture design of kakawate ash and cement ratio is to be recommended for construction of low-cost housing projects without sacrificing the strength of the structure.